2016
DOI: 10.5505/agri.2016.36024
|View full text |Cite
|
Sign up to set email alerts
|

Severe headache following ozone therapy: pneumocephalus

Abstract: ÖzetPnömosefali kranial kavitede havanın olmasıdır. Pnömosefali epidural anestezi veya epidural steroid enjeksiyonu sırasında yanlışlıkla duranın delinmesi ile meydana gelebilir. Olgumuz 41 yaşında kadın hasta, lomber disk hernisi tanısı ile opere olmuş fakat şikayetleri devam ediyordu başarısız bel cerrahisi sendromu olduğu düşünüldü. Ameliyathanede sedoanaljezi yapılarak steril koşullarda ve skopi altında RACZ kateteri kaudal bölgeden epidural alana yerleştirildi. İlk olarak Madrid deklarasyonu doğrul-tusund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…In addition, many studies have also reported on available scientific evidence concerning the beneficial properties of ozone therapy of pain, resulting in ozone therapy being widely used in pain management 19,20. However some complications of oxygen-ozone therapy still exist, such as headache pain, pneumocephalus, and cardiopulmonary arrest 21,22…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many studies have also reported on available scientific evidence concerning the beneficial properties of ozone therapy of pain, resulting in ozone therapy being widely used in pain management 19,20. However some complications of oxygen-ozone therapy still exist, such as headache pain, pneumocephalus, and cardiopulmonary arrest 21,22…”
Section: Introductionmentioning
confidence: 99%
“…Lo Giudice et al [ 57 ] reported a case of vitreous–retinal hemorrhages with bilateral visual loss after the intradiscal and periganglionic injection of O 2 -O 3 mixture for lumbar HD. Toman et al [ 58 ] presented a case of pneumocephalus, manifested by a rapidly evolving severe headache in patient who underwent percutaneous epidural neuroplasty combined with ozone treatment for FBSS. Vaiano et al [ 59 ] described a case of cortical blindness as a consequence of bilateral occipito-parietal lobe ischemia after the intradiscal and periganglionic O 2 -O 3 application at the L5/S1 level.…”
Section: Discussionmentioning
confidence: 99%
“…Rao et al reported a case of pneumocephalus in a 62-year-old female following an epidural injection of bupivacaine and ozone for the treatment of a prolapsed disc (27). Toman et al demonstrated that the use of ozone and ozonated growth factors in the treatment of disc prolapse was carried out in 60 patients, with only two reported cases of pneumocephalus (28).…”
Section: Discussionmentioning
confidence: 99%